Advertising procedure - Verril, Glenn; Russel, J. Thomas (Tenth Edition, 1986)
Los temas principales de este texto son: The fragmented television audience: television as an advertising medium: the rating-point system: share af audence: the many faces of television: the syndicated research services: summmary.
Incluye bibliografía
Keywords: Publicidad; Servicios